Structural, electronic structure and antibacterial properties of graphene-oxide nano-sheets - Sharma, Aditya; Varshney, Mayora; Nanda, Sitansu Sekhar; Shin, Hyun Joon; Kim, Namdong; Yi, Dong Kee; Chae, Keun-Hwa; Won, Sung Ok (ELSEVIER SCIENCE BV, 2018)
Correlation between the structural/electronic structure properties and bio-activity of graphene-based materials need to be thoroughly evaluated before their commercial implementation in the health and environment precincts. To better investigate the local hybridization of sp(2)/sp(3) orbitals of the functional groups of graphene-oxide (GO) and their execution in the antimicrobial mechanism, we exemplify the antibacterial activity of GO sheets towards the Escherichia coli bacteria (E. coli) by applying the field-emission scanning electron microscopy (FESEM), near edge X-ray absorption fine structure (NEXAFS) and scanning transmission X-ray microscope (STXM) techniques. C K-edge and O K-edge NEXAFS spectra have revealed lesser sp(2) carbon atoms in the aromatic ring and attachment of functional oxygen groups at GO sheets. Entrapment of E. coli bacteria by GO sheets is evidenced by FESEM investigations and has also been corroborated by nano-scale imaging of bacteria using the STXM. Spectroscopy evidence of functional oxygen moieties with GO sheets and physiochemical entrapment of E. coli bacteria have assisted us to elaborate the mechanism of cellular oxidative stress-induced disruption of bacterial membrane. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: X-RAY MICROSCOPY; CELLS